Pemeliharaan Lereng Pada Ruas Jalan Nasional Cikembang – Bagbagan Berdasarkan Kategori Risiko - Muhammad Dhaffa Dhiya Kamil; Imam Aschuri (Jurnal Serambi Engineering, 2023)
The incidence of landslides increases during the rainy season, especially in hilly areas or valleys. Cikembang - Bagbagan road is a national road that connects Pelabuhanratu - Sukabumi City with the condition of the area in the form of hilly areas with many slopes. This study aims to assess the level of slope risk and mitigation recommendations needed. The data collection method used is using secondary data in the form of inspection data and inventory of related slopes. The analysis method was carried out by determining the index value based on the Guidelines for road slope risk assessment (2018) and then analyzed to obtain the risk category. The results of 4 slopes obtained 2 slopes with high risk, 1 slope with medium risk, and 1 slope with low risk. In the risk assessment, the parameters of engineering buildings, geometry and geology of slopes play a major role in determining the risk category. Mitigation carried out on the 4 slopes is carried out in accordance with the risk category such as routine maintenance, rehabilitation, and slope instrumentation. The mitigation prioritization is done first on slope D then slope A, slope B, and slope C.